Teaching Strategies as Predictors of Students' Mathematics Interest among O-Level Students in Wakiso District, Uganda - Kirabo, Nkambwe Nakasiita; Olema, David; Baguwemu, Ali; Kibedi, Henry (East African Journal of Health and Science, 2023)
Interest in Mathematics is a factor that most educators are interested in because of its impact on mathematics learning, and teachers are considered key players in fostering students' interest in mathematics. The study investigated the predictive effect of perceived teaching strategies on students' interest in mathematics among O-level students in the Wakiso district. A mixed methods approach was used; 332 Senior Three students in total were used for the quantitative data, six students from each school took part in focus group discussions (FGDs), and one O-level mathematics teacher from each school was a key informant for the qualitative data. The findings revealed that teacher-centred strategies did not significantly predict overall interest, individual interest, and situational interest in mathematics, learner-centred strategies positively predicted overall interest and individual interest in mathematics and did not significantly predict situational interest, student-teacher interactive strategies positively predicted overall interest, individual interest and did not significantly predict situational interest. The qualitative results confirmed the quantitative results complemented the qualitative results. The study concluded that teachers need to develop more innovative strategies that can tap into students' interests in mathematics lessons and overall interest in mathematics